Maintaining a positive patient experience during COVID-19 in a rehabilitation and complex care setting - Sarah Benn Orava; Kim Cook; Amanda Brown (The Beryl Institute, 2020)
West Park Healthcare Centre located in Toronto, Ontario, Canada provides specialized rehabilitative and complex care after a life‐altering illness or injury such as lung disease, amputation, stroke and traumatic musculoskeletal injuries. This narrative showcases the strategies, processes and the lessons learned and subsequently utilized throughout the COVID-19 pandemic to engage patients and their family and peers. Experience Framework This article is associated with the Patient, Family & Community Engagement lens of The Beryl Institute Experience Framework. (http://bit.ly/ExperienceFramework) <a href="https://www.theberylinstitute.org/page/PXSEARCH#resource-list-all/?view_28_page=1&view_28_filters=%5B%7B%22field%22%3A%22field_38%22%2C%22operator%22%3A%22in%22%2C%22value%22%3A%5B%22PXJ%20Article%22%5D%7D%2C%7B%22field%22%3A%22field_20%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%2C%7B%22field%22%3A%22field_40%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%2C%22Patient%2C%20Family%20%26%20Community%20Engagement%22%5D%7D%2C%7B%22field%22%3A%22field_41%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%5D">Access other PXJ articles related to this lens. Access other resources related to this lens.